Insights into the initiation of JC virus DNA replication derived from the crystal structure of the T-antigen origin binding domain. - Gretchen Meinke (Public Library of Science (PLoS), 2014)
JC virus is a member of the Polyomavirus family of DNA tumor viruses and the causative agent of progressive multifocal leukoencephalopathy (PML). PML is a disease that occurs primarily in people who are immunocompromised and is usually fatal. As with other Polyomavirus family members, the replication of JC virus (JCV) DNA is dependent upon the virally encoded protein T-antigen. To further our understanding of JCV replication, we have determined the crystal structure of the origin-binding domain (OBD) of JCV T-antigen. This structure provides the first molecular understanding of JCV T-ag replication functions; for example, it suggests how the JCV T-ag OBD site-specifically binds to the major groove of GAGGC sequences in the origin. Furthermore, these studies suggest how the JCV OBDs interact during subsequent oligomerization events. We also report that the OBD contains a novel "pocket"; which sequesters the A1 & B2 loops of neighboring molecules. Mutagenesis of a residue in the pocket associated with the JCV T-ag OBD interfered with viral replication. Finally, we report that relative to the SV40 OBD, the surface of the JCV OBD contains one hemisphere that is highly conserved and one that is highly variable.